Detection of Bacteria Related to Periodontal Disease in Oral Cavity of Japanese Children by Species-specific PCR - IDA, Hiroshi; IGARASHI, Takeshi; INOUE, Mitsuko; GOTO, Nobuichi; HASEGAWA, Koji; SUZUKI, Motoyuki; SASA, Ryuji; YAN, Ni Xue (The Journal of Showa University Dental Society, 2004)
The purpose of this study was detect the presence of four putative periodontopathic bacteria Porphyromonas gingivalis (P. g.), Actinobacillus actinomycetemcomitans (A. a.), Prevotella intermedia (P. i.), and Bacteroides forsythus (B. f) using PCR in the oral cavities of children, then investigated relationships between bacterial species and various clinical parameters. The subject of 37 children were enrolled the pediatric dental clinic at the Showa University Dental Hospital in Japan. Children with systematic diseases were not excluded, although no subjects who had taken antibiotics within the past 3 month were included. A supragingival plaque sample was collected from the mesiobuccal and labial surfaces of the right maxillary central incisor (FDI 11) and the right maxillary first molar (FDI 16). Extracted DNA from plaque samples was used for PCR in this study. The amplification products were photographed under UV illumination. The following clinical parameters were also assessed : intraoral examination, probing depth (PD) and Bleeding On Probing (BOP). In this study, detection rate for P. g. was 21.6% and A. a., P. i. and B. f were detected from 55% to 58% in supragingival plaque. All subjects were not periodontitis. In addition, detection rates for A. a., P. i. and B. f were high in children with mixed dentition, but low in those with permanent dentition. Furthermore, regarding the relationship between bacterial species and BOP, it was not regarded between P. g. and BOP. Detection rates of A. a., P. i. and B. f were higher for BOP (+) than for BOP (-). Detection rates of putative periodontopathic bacteria from healthy children 6-18 years of age was higher in this study. The result suggest that it was need searching of children had a high risk facter for periodontal disease in childhood.